Identification of differences in height, weight, and body mass index based on playing position in amateur female football athletes - Arfiansyah, Eggy Nur; Koba, Kristoforus Nono; Habiburrahman, Fauzan Asa; Wicaksono, Surya Rihadi; Pinem, Swandika (Universitas Negeri Malang, 2024)
Background: Research interests in women's football has increased over recent years. Several factors can influence a woman's fitness level, including body composition (height, weight, and body mass index). Knowledge of anthropometry can help assess and evaluate the specifics of training programs. This is to identify players who may be considered necessary to successfully implement tactical roles and reference norms for developing future football-playing talent. Objective: This study aimed to identify differences in height, weight, and body mass index based on playing positions of female amateur football athletes. Methods: The population and sample in this study were 24 amateur female football players, and the research design used a measurement test. One-way ANOVA was used to test the difference in each variable. Result: The results show significant differences between the variables tested based on the player's position in the team, which could not be determined with significant results for the height variable of 0.738 > 0.05, then for the weight value of 0.213 > 0.05, and the BMI variable of 0.213 > 0.05. 0.143 > 0.05. Conclusion: This finding concludes that there are no significant differences in height, weight, and BMI in amateur women football players based on playing position. However, players must maintain ideal body proportions to support physical performance during matches or competitive seasons.